THE ROLE OF DATA JOURNALISM IN INFORMING PUBLIC FACTS: A CASE STUDY OF WHOOSH HIGH-SPEED TRAIN NEWS IN ONLINE MEDIA (KOMPAS.COM, TEMPO.CO, AND DETIK.COM) - Juhansyah Juhansyah; Arham Selo; Anshar Akil (PT Altin Riset Publishing, 2025)
The rapid development of digital media has accelerated the flow of information about national strategic infrastructure projects, including the Whoosh High Speed Train in Indonesia. This condition increases the risk of information flooding and the emergence of unverified data claims, thus confirming the importance of the role of data journalism in conveying public facts accurately and transparently. This study aims to examine the role of data journalism in the news of the Whoosh High Speed Train in online media by analyzing how data is collected, verified, analyzed, and presented by three national online media, namely Kompas.com, Tempo.co, and Detik.com. This study uses a qualitative approach with a case study design. The analysis technique used is a qualitative content analysis of selected news that contains data elements. The analysis was carried out using the data journalism framework of Gray, Chambers, and Bounegru, and was associated with gatekeeping and verification theories as well as media innovation theories. The results of the study show that there is significant variation in the application of data journalism in the three media. Tempo.co demonstrate the most comprehensive application of data journalism, characterized by a diversity of data sources, consistent verification practices, in-depth data analysis, and the use of analytical visualization. Kompas.com show a moderate level of adoption with a balance between the use of data and the context of the narrative, while Detik.com tend to use data descriptively and minimally with an emphasis on the speed of news presentation. This study concludes that data journalism plays an important role in improving the quality of public information when applied as a systematic journalistic process, not just as a complement to numbers. The effectiveness of data journalism is greatly influenced by the capacity of the newsroom, editorial orientation, and the level of innovation of the media organization. This study contributes to the study of data journalism and digital journalism by showing how editorial decisions and media innovation shape the epistemic quality of news infrastructure in the digital era.